THE WAYS OF IMPROVEMENT OF POWER EFFICIENCY OF INDUSTRIAL FURNACES AT RECUPERATION OF HEAT OF OUTGOING SMOKE - V. I. Timoshpolskiy; I. A. Trusova; D. V. Mendelev (Литьë и металлургия)
The main schemes of recovery of waste gases heat, applied in fuel furnaces of metallurgical and machinebuilding production, are analysed, and also criteria of choice of recuperators construction depending on function and constructions of furnaces are considered.